106 Cardiovascular Disease Outcomes Strategy Drives Improved Survival for Patients with Out-of-hospital Cardiac Arrest. (3rd June 2016) - Johnson, Shona; Horne, Stephanie; Realey, Tracey; Keating, Liza; Orr, William
Abstract : Background: NHS statistics show that Emergency Medical Services (EMS) attend nearly 60 000 patients with out-of-hospital cardiac arrest (OOHCA) in England each year and attempt cardiopulmonary resuscitation (CPR) in approximately 28000 cases. The chances of survival are improved by an immediate call for help, early bystander CPR and defibrillation, rapid transfer to hospital and early access to intensive care, 24/7 emergency coronary intervention when indicated and other supportive measures. The Cardiovascular Disease Outcomes Strategy calls for a range of measures across this pathway that will lead to improved survival rates in the UK. This triggered a series of local public education initiatives, closer working between the ambulance service, emergency department (ED), cardiology and intensive care, and a new protocol for these patients delivering more aggressive use of angiography and PCI in order to achieve better outcomes. Method: We analysed ambulance service data, ED records, local MINAP and Trust coding data to identify 3428 patients over 32 months who presented with OOHCA in our catchment area (population c.550 000), in whom CPR was started or continued, and who survived to arrival at hospital. Outcomes in hospital were recorded for each patient and compared with NHS England statistics. Results: 22% of patients arriving at RBH with OOHCA went to the cath lab with 62.4% survival v 7.3% for the rest (p < 0.001). 49% of patients transferred to the cath lab underwent PCI (no difference in rates between admission routes) with a trend towards better survival rates compared to those undergoing angiography alone (67.7% v 50%, ns). Conclusions: Patients with OOHCA treated by South Central Ambulance Service (SCAS) have a significantly better chance of survival to discharge than the average for England with a trend towards even better survival at our hospital. This difference may be due to our targeted working with SCAS on pathways for OOHCA and the high likelihood across this region of patients being taken directly to a heart attack centre. Patients requiring airway management or ongoing CPR on arrival at RBH are taken to ED for stabilisation prior to cath lab transfer, but the mortality of those coming to the cath lab via this route with the additional delay is not statistically different from those with direct admission. Patients who present to our hospital with out-of-hospital cardiac arrest and survive to the cath lab are a self-selecting group who, with current best care, have a very good chance of survival. Ongoing work will guide further refinement of these treatment pathways.